2007
DOI: 10.1063/1.2714297
|View full text |Cite
|
Sign up to set email alerts
|

H-mode pedestal and threshold studies over an expanded operating space on Alcator C-Mod

Abstract: This paper reports on studies of the edge transport barrier and transition threshold of the High field at constant current, but the operational space at high B shifts towards higher temperature and lower density and collisionality. Experiments with reversed field and current show that scrape-off-layer flows in the high field side depend primarily on configuration. In configurations with the B×∇B drift away from the active X-point, these flows lead to more counter-current core rotation which apparently contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 34 publications
9
35
1
Order By: Relevance
“…Similar transient increases of edge electron temperature [10] and improved L-mode energy confinement [5] have been reported on CMod. Threshold studies on these tokamaks, as well as DIII-D, showed clearly that edge temperatures, T gradients and required heating power are substantially higher at the L-H transition in the unfavorable vs. favorable ∇B configuration [11][12][13][14].…”
Section: Introductionsupporting
confidence: 78%
“…Similar transient increases of edge electron temperature [10] and improved L-mode energy confinement [5] have been reported on CMod. Threshold studies on these tokamaks, as well as DIII-D, showed clearly that edge temperatures, T gradients and required heating power are substantially higher at the L-H transition in the unfavorable vs. favorable ∇B configuration [11][12][13][14].…”
Section: Introductionsupporting
confidence: 78%
“…The higher local Te threshold and multi-step dynamics with unfavorable drift were later studied in more detail. 178 These early observations suggests that the I-mode is not an exotic and elusive regime, but is rather a standard behavior under suitable conditions. Figure 28 shows time traces from a typical I-mode and illustrates the salient characteristics.…”
Section: I-modementioning
confidence: 99%
“…I-mode is typically accessed in the "unfavorable" drift configuration -that is, with ion ∇B drift directed away from the primary X-point [20]. This elevates the H-mode threshold power [40], widening the range over which I-mode can be sustained. This drift configuration has been achieved both with standard field and current in an upper-null shape, and in a lower-null shape with reversed field and current.…”
Section: I-mode Access and Experimental Setupmentioning
confidence: 99%